SINERGI INTERDISIPLINER MENUJU KEMANDIRIAN MELALUI PENGABDIAN MASYARAKAT DI DESA SUNGAI NIPAH, KABUPATEN MEMPAWAH - Bapuaka, Marselus Sule; Wagner, Ivan (Dianmas Bhakti: Jurnal Pengabdian pada Masyarakat, 2025)
The Community Service Program (KKN) of Group 15 from Panca Bhakti University in Sungai Nipah Village was designed to foster village independence through a holistic and participatory approach. The program addressed key challenges, including limited digitalization among local MSMEs, farmers' reliance on conventional agricultural methods, low legal literacy, and insufficient awareness of environmental preservation. Implementation was carried out in collaboration with the village government and community, focusing on education, infrastructure, and agriculture. Key outcomes included enhanced legal awareness through the "law-conscious village" campaign, improved digital economy skills via training on e-commerce platforms and non-cash transactions, as well as anti-bullying initiatives. In agriculture, productivity was supported through the introduction of bird pest repellent tools and the establishment of farmer group signboards. Environmental awareness was strengthened with educational signboards promoting waste management. The program's success was marked by strong community and government participation. Overall, this KKN initiative contributed not only to tangible improvements in the village's physical and non-physical development but also to the establishment of sustainable partnerships for long-term progress